PENERAPAN METODE JARIMATIKA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SDN 003 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Sitio, Tiarmina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this research is the poor performance of student mathematics learning class I SDN 003 Tagaran Tapah Darussalam. The low yield of this study was due to: (a) from 24 students only 8 people are visible in following the spirit of the learning process; (b) the interest of students in the teacher's task is still lacking, it is seen when given the job of more than 50% of students do not do a good job; (c) visible from 24 students only 40% who responded to the question posed by the teacher; and (d) if no problems are considered difficult, low-ability students who are just waiting for the result of his highly capable, without any attempt to resolve the matter. For that research by applying the method Jarimatika with the aim of improving the results of students' mathematics learning. This research is a classroom action research was conducted in two cycles in cycle I and cycle II, each cycle is done in two sessions, the steps of this study consists of four stages: (1) planning; (2) the implementation of the action; (3) observation; and (4) reflection. Based on observations prior to the application of the method jarimatika student learning outcomes at baseline before treatment, learning outcomes of students obtained an average percentage of 66.88% with a fairly high category. Then based on the observation of the first cycle which indicates that the level of student learning outcomes reached with an average percentage of 69.79% with a high category. While on the second cycle increased achieving student learning outcomes obtained an average percentage of 78.54% with a high category.